(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In this paper the synthesis of oligomers containing sulfur, phosphorus and nitrogen were studied of optimum conditions. The obtained oligomers were used as polyethylene fillers, and the effect on the physicochemical properties of polyethylene was studied. Also, the thermal stability of polyethylene filled with fillers after the addition of fillers was analyzed using TGA and TDA analyses. According to the obtained results, it was found that these oligomers improved the thermal physical-chemical properties of polyethylene.